(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Microbial contamination in operation theaters (OT) represents a critical risk factor for surgical site infections (SSIs) and adverse patient outcomes. Chemical fumigation using formalin and newer agents like Alpha Guard are employed for environmental decontamination, but comparative effectiveness data remain limited in tertiary care settings. Objective: This study compared the efficacy of Alpha Guard and formalin fumigation in reducing microbial contamination in operation theaters using pre- and post-intervention microbial sampling. Methods: A cross-sectional comparative study was conducted in a 600-bed tertiary care hospital. Pre-fumigation and post-fumigation microbial samples (n=240) were collected from five operation theaters over 12 weeks. Sampling locations included air, surfaces, and equipment. Colony-forming units (CFU) were enumerated and identified using standard microbiological techniques. Data were analyzed using SPSS v27.0 with paired t-tests, independent t-tests, and descriptive statistics. Results: Alpha Guard fumigation demonstrated superior microbial reduction compared to formalin across all parameters. Mean CFU reduction in air samples: Alpha Guard 94.2% vs. Formalin 78.3% (p<0.001). Surface contamination reduction: Alpha Guard 96.1% vs. Formalin 81.5% (p<0.001). Equipment surface reduction: Alpha Guard 95.8% vs. Formalin 79.2% (p<0.001). Bacterial species identified included Staphylococcus aureus (35.2%), Bacillus species (22.8%), and Aspergillus species (18.4%). Alpha Guard demonstrated significantly faster microbial elimination (mean 4.2 hours) compared to formalin (mean 8.7 hours, p<0.001). Sustained efficacy at 72-hour post-fumigation was superior for Alpha Guard (89.3%) versus formalin (64.2%, p<0.001). Conclusions: Alpha Guard fumigation exhibits superior efficacy in reducing microbial contamination in operation theaters compared to formalin, with faster decontamination kinetics and superior sustained efficacy. Implementation of Alpha Guard fumigation protocols may significantly reduce SSI risk and improve surgical safety outcomes in tertiary care settings.